2009
DOI: 10.1159/000254482
|View full text |Cite
|
Sign up to set email alerts
|

Increased Amount of Visceral Fat in Patients with Psoriasis Contributes to Metabolic Syndrome

Abstract: Background: Psoriasis is associated with obesity and metabolic syndrome. Metabolic syndrome is associated with visceral fat accumulation. There is no study on the accumulation of visceral fat in patients with psoriasis. Objective: The aim of this study was to compare the visceral fat accumulation in patients with psoriasis and controls. Subjects and Methods: 46 patients with psoriasis and 46 sex- and age-matched control patients were included in this study. The abdominal fat area [visceral fat area (VFA), subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 47 publications
1
42
2
Order By: Relevance
“…Balci et al 2010 demonstrated that visceral fat area (VFA) is increased in psoriatic patients and is associated with the presence of psoriasis [21]. They also demonstrated that VFA is associated with the presence of metabolic syndrome in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Balci et al 2010 demonstrated that visceral fat area (VFA) is increased in psoriatic patients and is associated with the presence of psoriasis [21]. They also demonstrated that VFA is associated with the presence of metabolic syndrome in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-abdominal obesity is directly linked to the metabolic syndrome, and visceral fat is an endocrine organ capable of secreting multiple bioactive adipocytokines promoting inflammation and affecting glucose metabolism and vascular endothelial biology. Psoriasis patients have a higher amount of visceral fat, compared with the control patients [26]. Adipose tissue TNF-α mRNA correlates with BMI, percentage of body fat and hyperinsulinemia [27].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there are reports of remission of severe psoriasis as a result of gastric bypass surgery [14,15,16], or in patients forced to severe dietary restriction [33]. Fasting periods, vegetarian diets and diets rich in n–3 polyunsaturated fatty acids from fish oil have been associated with psoriasis improvement in some noncontrolled studies [26,33]. More recently, we have shown in a randomized controlled study that obese patients with moderate-to-severe psoriasis increase their response to low-dose cyclosporine if a calorie-controlled diet is included in the treatment regimen [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been suggested that treatment with tumour necrosis factor (TNF) inhibitor or hydroxychloroquine may reduce the risk of diabetes in both psoriasis and RA, although formal trial evidence is lacking 23. Consistent with the greater risk of diabetes, patients with psoriasis appear to have increased amounts of visceral fat 24. Furthermore, non-alcoholic fatty liver disease (NAFLD) is almost twice as prevalent in patients with psoriasis compared with BMI-matched controls without psoriasis 25.…”
Section: Cardiometabolic Disorders In Psoriasis and Psamentioning
confidence: 99%